Weakly Supervised Learning for Categorization of Medical Inquiries for Customer Service Effectiveness - Singhal, Shikha; Hegde, Bharat; Karmalkar, Prathamesh; Muhith, Justna; Gurulingappa, Harsha (Frontiers in Research Metrics and Analytics, 2021)
With the growing unstructured data in healthcare and pharma, there has been a drastic adoption of natural language processing for generating actionable insights from text data sources. One of the key areas of our exploration is the Medical Affairs function within our organization. We receive a significant amount of medical information inquires in the form of unstructured text. An enterprise level solution has to deal with medical information interactions via multiple communication channels which are always nuanced with a variety of keywords and emotions that are unique to the pharma industry. There is a strong need for an effective solution to leverage the contextual knowledge of medical information business along with digital tenants of natural language processing (NLP) and machine learning to build an automated and scalable process that generates real time insights on conversation categories. The traditional supervised learning methods rely on huge set of manually labeled training data and this dataset is difficult to attain due to high labeling costs. Thus, the solution is incomplete without its ability to self-learn and improve. This necessitates techniques to automatically build relevant training data using weakly supervised approach from textual inquiries across consumers, healthcare professionals, sales, and service providers. The solution has two fundamental layers of NLP and machine learning. The first layer leverages heuristics and proprietary knowledgebase to identify the potential categories and build an annotated training data. The second layer, based on machine learning and deep learning, utilizes the training data generated using the heuristic approach for identifying categories and sub-categories associated with verbatim. Here, we present a novel approach harnessing the power of weakly supervised learning combined with multi-class classification for improved categorization of medical information inquiries.